THE SPECIFICS OF MOTOR ABILITIES OF FOOTBALL PLAYERS IN RELATION TO THE RANK OF COMPETITION - Ljubiša Lilić; Dragana Aleksić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2012)
The knowledge of the high coeficient of the correlation between the success in sports and sports capacities primarily determined by psychosomatic status decided on the subject of this work. To be precise, the subject of this work represents the identification of the dominant basic and specific motor dimensions of football players of two ranks of competitions which participate in sports success in football, and recognition of quantitative and qualitative indices which differentiate them. The results of the discriminative analysis of specific motor variables show that the football players of higher rank of competition statistically significantly differ from the football players of lower rank of competition. The coefficient of the canonical correlation amounts .99. The significance of this correlation tested by the Wilks' test and Bartlett's CH-i test with 13 degrees of freedom shows highly significant differencies between the groups of tested athletes because the sig. =.00, and the results CH = 41.25 per one got root.